Research on Concept Model Framework Construction for Traditional Chinese Medicine on"Recognition Function" - Xiaoling LI; Danhong LIN (康复学报)
Objective:To construct a concept model framework for traditional Chinese medicine on"recognition function", and realize the specification, utilization and management of the concepts and items of traditional Chinese medicine of"recognition function".Methods:The modeling method for the concept model of analysis-description-validation was adopted.﹡Analysis: The understanding of traditional Chinese medicine on"recognition function"was used to analyze its related field and category.﹡Description: According to the guidance principles and construction principles of model, Protégé construction tool was used to organize the knowledge information in the form of tree framework.﹡Validation: The framework of concept model was consulted and demonstrated.Results:Concept model framework for traditional Chinese medicine on"recognition function"which included five top-level categories, 23 second level of categories and 75 third level of categories was created.Conclusion:Construction of concept model framework for traditional Chinese medicine on"recognition function"has made a initial exploration for the building of the concept model for traditional Chinese medicine on"recognition function", and provided a useful reference for the term system construction of science of rehabilitation of traditional Chinese medicine.